2023
DOI: 10.1177/13524585221150881
|View full text |Cite
|
Sign up to set email alerts
|

Safety of COVID-19 vaccines in multiple sclerosis: A systematic review and meta-analysis

Abstract: Background Data are sparse regarding the safety of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines in patients with multiple sclerosis (MS). Objective To estimate (1) the pooled proportion of MS patients experiencing relapse among vaccine recipients; (2) the rate of transient neurological worsening, adverse events, and serious adverse events; (3) the previous outcomes of interest for different SARS-CoV-2 vaccine types. Methods Systematic review and meta-analysis of pharmacovigilance regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Finally, a recent meta-analysis of 19 studies gathering more than 14,000 MS patients concluded that COVID-19 vaccination was not associated with an increased risk of disease activity. 28 Conversely, two reports 20,25,27 and one case series 22 of 16 patients described MS relapses shortly after COVID-19 vaccination. Still, the timing between the vaccination and relapse occurrence was often very short, raising the question of a true causality between the two events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a recent meta-analysis of 19 studies gathering more than 14,000 MS patients concluded that COVID-19 vaccination was not associated with an increased risk of disease activity. 28 Conversely, two reports 20,25,27 and one case series 22 of 16 patients described MS relapses shortly after COVID-19 vaccination. Still, the timing between the vaccination and relapse occurrence was often very short, raising the question of a true causality between the two events.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a recent meta-analysis of 19 studies gathering more than 14,000 MS patients concluded that COVID-19 vaccination was not associated with an increased risk of disease activity. 28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, only 4.4% (99/2261) of patients experienced a relapse after vaccination. A recent systematic review and meta-analysis of 19 studies comprising 14,755 SARS-CoV-2-vaccinated patients with MS also found that the pooled proportion of MS patients with relapse after vaccination was only 1.9% [16]. Moreover, the proportion of patients with serious adverse events was as low as 0.1%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, vaccination is a complex issue in this population considering that these patients are frequently subjected to immunomodulatory or immunosuppressive treatments. A number of recent studies of patients with MS have shown that COVID-19 vaccination does not increase the risk of clinical relapse and serious adverse events, suggesting favorable safety of COVID-19 vaccine in MS patients [14][15][16]. The issue of immunogenicity of COVID-19 vaccines in relation to MS medications has also been evaluated in some studies [17,18].…”
Section: Introductionmentioning
confidence: 99%